Pengetahuan dan Perilaku Ibu Rumah Tangga Dalam Penggunaan Garam Beryodium Di Kelurahan Tosaren Kota Kediri - Oktaviasari, Dianti Ias (Pena Medika Jurnal Kesehatan, 2021)
Iodine Deficiency Disorders (IDD) are a group of symptoms caused by the body being deficient in iodine for a long time. IDD is a serious problem and has a bad impact, so it needs good treatment, one of which is by iodization or fortification of all salts with potassium iodate (KOI3) or Universal Salt Iodization (USI). The national target has not yet reached the target of achieving USI by WHO (90%) and the target coverage of the National Action Plan for Food and Nutrition (RANPG) 2011-2015 (80%). The purpose of this study was to describe the knowledge and behavior of housewives in the use of iodized salt. This research is a cross sectional study. The population in this study were housewives in Tosaren Village, Kediri, who got 588. The sampling technique was taken by simple random sampling with the criteria of being able to fill out a google form and be willing to be a respondent. The sample size in this study was 85 housewives. The results showed that the knowledge of housewives about iodized salt in Tosaren Village, Kediri City was mostly good. The attitude towards the use of iodized salt most of the housewives agree with the use of iodized salt. The behavior of almost all housewives has used iodized salt for daily consumption. Good knowledge is in line with attitudes and behaviors in the use of iodized salt by housewives. Keywords: Iodized salt, knowledge, behavior, housewives